Mobile health application platform 'Corrie' personalises and empowers the heart attack recovery patient experience in the hospital and at home for an underserved heart attack survivor. Issue 2 (17th February 2020) - Hung, George; Yang, William E; Marvel, Francoise A; Martin, Seth S
Abstract : Cardiovascular disease (CVD) is the leading cause of morbidity and mortality worldwide with an estimated 17.5 million deaths annually, according to the World Health Organization (WHO). CVD prevention efforts have the potential to prevent the majority of these deaths by supporting guideline-directed medical therapy (GDMT) and lifestyle modification. Mobile health (mHealth) has the potential to address this gap, but has limited evaluation in clinical studies to date. We present the case of a middle-aged patient of low socioeconomic status, with multiple comorbidities, and no prior smartphone experience, who suffered an acute myocardial infarction (MI) and was given the Corrie intervention while hospitalised. The patient demonstrated improvement in lifestyle modification, adherence to GDMT and post-MI recovery through 2.4 years follow-up. This case supports (1) the potential of mHealth interventions to enhance patient experience and outcomes, (2) intuitive design for adoption and improvement in end user experience and (3) the capability of mHealth to reach and empower underserved patients.